Yellow light improves milk quality, antioxidant capacity, immunity, and reproductive ability in dairy cows by elevating endogenous melatonin - Shen, Zixia; Wang, Weijia; Liu, Xuening; Shan, Xiangao; Wu, Hao; Li, Guangdong; Yao, Songyang; Liu, Yunjie; Yan, Laiqing; Ji, Pengyun; Wang, Bingyuan; Liu, Guoshi (Frontiers in Veterinary Science, 2026)
BackgroundLight is an important environmental factor influencing animal production. In livestock production, light management techniques are common. They can enhance production and reproductive performance.AimThis study investigated the effects of light wavelength on dairy cows. It focused on production, immunity, antioxidant capacity, and reproduction. It emphasized yellow light.MethodologyIn Experiment 1, 196 cows were divided into three groups and subjected to natural dark, red, and yellow light for 2 weeks. Results indicated yellow light was most effective. This prompted a second experiment. In Experiment 2, 80 postpartum cows received nocturnal yellow light until their next calving. Blood and milk samples were analyzed for immune, antioxidant, and reproductive markers.ResultsThe findings demonstrated that yellow light significantly enhanced milk yield (32.39–37.58 kg) and composition, including milk fat percentage, milk protein percentage, lactose percentage, milk urea nitrogen, and somatic cell count. It improved immune status (TNF-α: 181.10–174.90 pg/ml, IL-6: 117.30–113.90 pg ml, IL-10: 31.18–32.86 pg/ml), antioxidant status (superoxide dismutase: 111.80–117.60 U/ml, total antioxidant capacity: 8.28–8.76 U/ml), and superior reproductive performance (the interval to first postpartum estrous cycle: 61.72 ± 1.27 to 56.91 ± 1.14 days, the pregnancy rate after first-insemination: 23.68 ± 4.42% to 38.15 ± 5.00%, the pregnancy days after first-insemination: 96.84 ± 4.88 to 82.95 ± 4.50 days). This was associated with enhanced melatonin levels in serum (36.30–59.48 pg/ml) and milk (20.49–29.22 pg/ml).ConclusionNocturnal yellow light exposure, by elevating endogenous melatonin, is a viable non-invasive strategy to improve overall productivity, health, and welfare in dairy farming.